Rare Presentation of Epstein Barr Virus - Ari, Abhijit; Ghosh, Taraknath; Bose, Sayan; Shetty, Prashat Kumar; Chaudhary, Ruchi (Journal of Nepal Paediatric Society, 2016)
Two rare complication of infection with the Epstein-Barr virus is the development of hemophagocytic Lymphohistiocytosis and opsoclonus myoclonus syndrome. Here we are describing two cases which are describing these complications of Epstein-Barr virus infection. As they mimic several other condition but a strong suspicion is needed to diagnose these rare complications early as it will help us to reduce morbidity and mortality of these complications. J Nepal Paediatr Soc 2015;35(3):290-292